Innovative Energy Standard of Curative Cupping/Hijama - Asif Ahmed (Journal of Basic & Applied Sciences, 2015)
Objective:Cupping therapy (CT) is a therapeutic technique that has proved to be beneficial in array of human diverse plethora of ailments, has recently regained a significant gravity in present day medical practice. ACT (Asif Cupping Theory) of cupping therapy has been new therapeutic mold that explains the occult scientific dimensions of Cupping Therapy. Material & Methods:In the human physical body fundament electrical potentials generates from cell membranes. The ACT proposed that the application of negative vacuum pressure over the skin dot of low resistance or Quantum Orifice through the myofasical anatomical structure provides a meaningful access of cellular and organ energies that result in reorientation and dielectric relaxation. Results:Application of negative suction over specific Quantum Orifices over skin offers the access of specific organ in address. Additionally use of cuts over skin provides chance to filter out energies through evacuation of blood that itself contains water molecules as dielectric constant on one side and is physical molecular structure as condense energy on the other hand thus establish a linked to specific organ in address that results in the alleviation of pathogenic insult. Conclusion:ACT is novel quantum based energy model that successfully gives details that CT is a meaningful route based on electrical connectivity of deeper structure with quantum orifices present over the skin and application of negative vacuum and bloodletting facilitates the therapeutic expulsion of stagnated and intoxicated energy.